Method for manufacturing a titanium alloy with low cost and excellent corrosion resistance
A low-cost titanium alloy manufacturing method using HDH and post-heat treatment reduces porosity and stabilizes the β phase, enhancing mechanical properties and corrosion resistance.
Patent Information
- Application Number
- KR1020260017070
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2026-01-28
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2046-01-28
AI Technical Summary
Existing methods for manufacturing titanium alloys are costly and do not adequately address issues of porosity, which affect mechanical properties and corrosion resistance.
A method involving the preparation of titanium powder through hydrogenation-dehydrogenation (HDH) followed by mixing with Mo and Fe powders, compression molding, sintering, and post-heat treatment above the β transformation temperature to reduce porosity and stabilize the β phase.
The method results in a low-cost titanium alloy with improved mechanical properties and corrosion resistance, achieving porosity reduction to 20% or less and a Vickers hardness of 310 Hv or higher, with a corrosion current density of 1×10⁻⁸ A/cm².
Smart Images

Figure 112026011958871-PAT00007_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a method for manufacturing a titanium alloy through powder metallurgy, and more specifically, to a method for manufacturing a titanium alloy with controlled porosity through post-heat treatment using titanium powder produced by a low-cost hydrogenation-dehydrogenation process. Background Technology
[0003] Titanium and its alloys are widely used in various fields such as aerospace, biomaterials, chemical industry, and marine industry due to their advantages, including excellent mechanical properties, high corrosion resistance, and biocompatibility. In particular, β-Ti alloys have a body-centered cubic structure and possess characteristics such as a relatively low elastic modulus, high elongation, and excellent strength, making them a subject of interest as medical implants and structural materials. The problem to be solved
[0005] The present invention aims to provide a method for manufacturing a titanium alloy that is low-cost and has high corrosion resistance. means of solving the problem
[0007] To achieve the above objectives, a method for manufacturing a titanium alloy according to the present invention may include: (a) a step of preparing titanium powder through an HDH (hydrogenation-dehydrogenation) process; (b) a step of preparing a mixed powder by mixing the titanium powder with Mo powder and Fe powder; (c) a step of manufacturing a titanium alloy by compressing and sintering the mixed powder; and (d) a step of reducing porosity by post-heat treating the manufactured titanium alloy at a temperature above the β transformation temperature.
[0008] In addition, in a method for manufacturing a titanium alloy according to one embodiment of the present invention, the titanium alloy may consist of 2.0 to 7.0 wt% molybdenum (Mo), 1.5 to 5.0 wt% iron (Fe), and the remainder being titanium (Ti) and unavoidable impurities.
[0009] In addition, in a method for manufacturing a titanium alloy according to one embodiment of the present invention, the titanium alloy may consist of 4.0 to 6.0 weight% molybdenum (Mo), 3.5 to 4.5 weight% iron (Fe), and the remainder being titanium (Ti) and unavoidable impurities.
[0010] In addition, in a method for manufacturing a titanium alloy according to one embodiment of the present invention, the post-heat treatment may be performed in a temperature range of 800°C to 950°C.
[0011] In addition, in a method for manufacturing a titanium alloy according to one embodiment of the present invention, the post-heat treatment may be performed for 30 minutes to 4 hours.
[0012] In addition, in a method for manufacturing a titanium alloy according to one embodiment of the present invention, step (c) may include the step of compression molding the mixed powder and the step of sintering the compression-molded alloy at 1200°C to 1300°C.
[0013] In addition, in a method for manufacturing a titanium alloy according to one embodiment of the present invention, the porosity of the titanium alloy after the post-heat treatment may be reduced to 20% or less.
[0014] Meanwhile, according to the present invention, a titanium alloy can be provided that is manufactured through the titanium alloy manufacturing method described above and has a composition consisting of 2.0 to 7.0 wt% molybdenum (Mo), 1.5 to 5.0 wt% iron (Fe), and the remainder being titanium (Ti) and unavoidable impurities, and has a microstructure containing an equiaxed β phase, a porosity of 7% to 20%, and a Vickers hardness of 310 Hv or higher.
[0015] In addition, the corrosion current density (Icorr) of the above titanium alloy is 1×10 -8 It may be less than A / cm². Effects of the invention
[0017] Through the method for manufacturing a titanium alloy according to the present invention, it is possible to provide titanium that is low-cost, has excellent mechanical properties, and ensures corrosion resistance. Brief explanation of the drawing
[0019] Figure 1 is a scanning electron microscope image of commercial titanium powder and titanium powder used in one embodiment of the present invention. FIG. 2 is an optical microscope image of a titanium alloy before heat treatment according to one embodiment of the present invention. Figure 3 is an optical microscope image of a titanium alloy after heat treatment according to one embodiment of the present invention. Figure 4 is an optical microscope image of a titanium alloy after heat treatment according to one embodiment of the present invention. FIG. 5 is a graph showing the hardness measurement results of a titanium alloy after heat treatment according to one embodiment of the present invention. FIG. 6 is a graph showing the hardness measurement results of a titanium alloy after heat treatment according to one embodiment of the present invention. FIG. 7 is a potentiodynamic polarization curve of a titanium alloy after heat treatment according to one embodiment of the present invention. FIG. 8 is a potentiodynamic polarization curve of a titanium alloy after heat treatment according to one embodiment of the present invention. FIG. 9 is a potentiodynamic polarization curve of a titanium alloy after heat treatment according to one embodiment of the present invention. FIG. 10 is a potentiostatic polarization curve of a titanium alloy after heat treatment according to one embodiment of the present invention. FIG. 11 is a potentiodynamic polarization curve of a titanium alloy after heat treatment according to one embodiment of the present invention. Specific details for implementing the invention
[0020] Embodiments of the present invention are described below with reference to the attached drawings so that those skilled in the art can easily implement them. However, the present invention may be embodied in various different forms and is not limited to the embodiments described herein.
[0021] Throughout this specification, when a part is described as "comprising" a certain component, this means that, unless specifically stated otherwise, it does not exclude other components but may include additional components.
[0022] As used herein, terms of degree such as “about,” “substantially,” etc., are used to mean at or near the stated value when inherent manufacturing and material tolerances are presented in the stated meaning, and are used to prevent unscrupulous infringers from unfairly exploiting the disclosure in which precise or absolute values are mentioned to aid in understanding the invention. Furthermore, throughout this specification, “a step of” or “a step of” does not mean “a step for”.
[0023] Throughout this specification, the term “combination thereof” included in the Markush-type expression means one or more mixtures or combinations selected from the group consisting of the components described in the Markush-type expression, and means including one or more selected from the group consisting of said components.
[0024] Throughout the entire specification, the description "A and / or B" means "A or B, or, A and B".
[0025] A method for manufacturing a titanium alloy according to the present invention is characterized by comprising the steps of: preparing titanium powder through an HDH (hydrogenation-dehydrogenation) process; preparing a mixed powder by mixing the titanium powder with Mo powder and Fe powder; manufacturing a titanium alloy by compressing and sintering the mixed powder; and reducing the porosity by post-heat treating the manufactured titanium alloy at a temperature above the β transformation temperature.
[0026] In the present invention, a Ti-Mo-Fe alloy containing molybdenum (Mo) and iron (Fe) as alloying elements was selected to manufacture a β-Ti alloy composed of relatively low-cost alloying elements. Mo is a representative β-stabilizing element that improves corrosion resistance by forming MoO3, while Fe improves machinability, high-temperature stability, and toughness by increasing β-phase stability. The microstructure of the Ti-Mo-Fe alloy can vary significantly depending on the heat treatment conditions, and the final mechanical properties and corrosion resistance are determined accordingly. Accordingly, the Ti-Mo-Fe alloy in the present invention may consist of 2.0 wt% to 7.0 wt% molybdenum (Mo), 1.5 wt% to 5.0 wt% iron (Fe), and the remainder being titanium (Ti) and unavoidable impurities.
[0027] The hydrogenation-dehydrogenation (HDH) process applied in this invention is a method for producing high-purity titanium powder using low-cost titanium scrap as a raw material, and it enhances price competitiveness by recycling the scrap. In addition, moldability and other properties are secured by utilizing powder metallurgy (PM) technology.
[0028] The powder process technology first includes the step of preparing a mixed powder by mixing titanium powder produced through the HDH process with alloying element powders, such as Mo powder and Fe powder, to match the final composition, and then compression molding the mixed powder and sintering the compression-molded titanium alloy at 1200°C to 1300°C.
[0029] However, alloys manufactured using this PM method may exhibit poor mechanical properties due to residual porosity. Therefore, it is essential to apply an appropriate post-heat treatment process to reduce porosity and control the microstructure to ensure optimal mechanical and corrosion properties.
[0030] Post-heat treatment is essential for such a reduction in porosity. In the present invention, by performing post-heat treatment of the titanium alloy at a temperature above the β transformation temperature, the porosity is significantly reduced, and through an elemental composition that stabilizes the β phase, the titanium alloy comes to contain an equiaxed β phase.
[0031] The β-phase transformation temperature of the alloys can be calculated using the following equation (1), which is an empirical formula for the β-phase transformation temperature.
[0032] T β =872+23.4[Al]+32.1[Si]-7.7[Mo]-12.4[V]-14.3[Cr]-8.4[Fe]-4.3[Zr] Formula (1)
[0033] Preferred embodiments of the present invention will be described in detail below. However, the following embodiments are merely illustrative of the present invention, and the scope of the present invention is not limited by the following embodiments.
[0034] [Example]
[0035] Titanium powder was manufactured via the HDH process. The results of SEM observations to examine the morphology of the manufactured powder are shown in Figure 1. The particle size of the developed titanium powder was 30.5 µm, which is approximately twice the size of commercial titanium powder (15.78 µm). Using HDH titanium powder, Mo powder with a particle size of 1–2 µm, and Fe powder with a particle size of 5–7 µm, a metastable β-type titanium alloy, Ti-5Mo-xFe (x=2.4 wt%), was fabricated using the PM method. The alloys were produced at 280 kg / cm² 2 After compression for 30 seconds, it was sintered under conditions of 1250℃, 6hr, FC to produce a size of 120 Х 10 Х 5 mm.
[0036] In this study, we aimed to obtain strength, ductility, and toughness by controlling the porosity to prevent residual pores present in alloys manufactured through powder processing technology from degrading mechanical performance, and to find optimal post-heat treatment conditions to maximize the reliability and mechanical performance of the material. The initial porosity of each alloy was high, ranging from 15 to 20%, and it appears that they will have poor mechanical properties as a result. To control the porosity of alloys with such high porosity, a post-heat treatment process was carried out, and to select post-heat treatment conditions, the β transformation temperature of the Ti-5Mo-xFe (x=2,4wt%) alloys was calculated using the above-described Equation (1).
[0037] As a result of calculating the β-transformation temperatures of each alloy, the Ti-5Mo-2Fe alloy was calculated to be approximately 816.7°C, and the Ti-5Mo-4Fe alloy was calculated to be approximately 799.9°C. Accordingly, post-heat treatment was performed on the two titanium alloys of different compositions that had completed sintering under six conditions as shown in Table 1 below.
[0038] Sample name Heat treatment temperature (°C) Heat treatment time (min) Ti-5Mo-2Fe Ti-52 - - Ti-52 #1 750 30 Ti-52 #2 750 120 Ti-52 #3 830 30 Ti-52 #4 830 120 Ti-52 #5 900 30 Ti-52 #6 900 120 Ti-5Mo-4Fe Ti-54 - - Ti-54 #1 750 30 Ti-54 #2 750 120 Ti-54 #3 830 30 Ti-54 #4 830 120 Ti-54 #5 900 30 Ti-54 #6 900 120
[0039] Microstructure, porosity, mechanical properties, and corrosion properties were evaluated on the fabricated Ti-5Mo-xFe (x=2~4wt%) alloy.
[0041] Porosity measurement
[0042] To measure the porosity of Ti-5Mo-xFe (x=2,4wt%) alloys according to Fe content and post-heat treatment conditions, the density was measured using the Archimedes method and the porosity of each was calculated, and the results are shown in Table 2.
[0043] Sample name Porosity (%), before heat treatment Porosity (%), after heat treatment Ti-5Mo-2Fe Ti-52 20 20 Ti-52 #1 17 16 Ti-52 #2 17 16 Ti-52 #3 17 15 Ti-52 #4 17 16 Ti-52 #5 16 13 Ti-52 #6 18 13 Ti-5Mo-4Fe Ti-54 17 17 Ti-54 #1 15 13 Ti-54 #2 14 12 Ti-54 #3 15 12 Ti-54 #4 15 11 Ti-54 #5 18 12 Ti-54 #6 15 7
[0044] of the manufactured alloys As a result of comparing the porosities, the decrease in porosity ranged from a minimum of 1% to a maximum of 8%. The decrease in porosity of the Ti-5Mo-4Fe alloy was measured to be relatively higher than that of the Ti-5Mo-2Fe alloy, which is interpreted as being due to the influence of the addition of the alloying element Fe. Fe is a eutectoid type As a stabilizing element, it possesses a relatively high diffusion coefficient within the titanium crystal lattice; as diffusion becomes more active, atoms rearrange along the pore walls, transforming into spherical pores with low curvature. During high-temperature diffusion, Fe atoms diffuse into or near the pores, and a phenomenon occurs in which atoms penetrate and fill the pores. The influence of the addition of the alloying element Fe and Due to the influence of post-heat treatment performed above the transformation point, the Ti-5Mo-4Fe #6 condition showed the highest reduction in porosity of about 8%.
[0045] Microstructure observation
[0046] Changes in the microstructure of Ti-5Mo-xFe (x=2,4wt%) alloys according to post-heat treatment conditions were observed using an optical microscope and a scanning electron microscope and are shown in Figures 2 to 4.
[0047] Microstructural observation results showed that the material prior to heat treatment exhibited an α+β lamellar structure of Widmanstätten A tten) structure was observed, and relatively large pores of approximately 19.35 µm were observed. Additionally, as the amount of Fe added increased, the spacing of the thin lamellar laths decreased from 3.51 ± 0.1 µm to 0.98 ± 0.3 µm. This is attributed to Fe increasing β-phase stability and rapidly diffusing at high temperatures to form a homogeneous β-phase, which delays or reduces the nucleation of the α-phase, thereby decreasing the spacing of the lamellar laths.
[0048] In the conditions of Ti-5Mo-2Fe #1 to #5 and Ti-5Mo-4Fe #1 and #2, which underwent post-heat treatment, a Widmanstätten microstructure with an α+β lamellar structure was observed, and a distinct decrease in lamellar spacing was observed as the temperature and time increased. In the case of Ti-5Mo-2Fe #6 and Ti-5Mo-4Fe #3 to #6, an equiaxial β phase was observed, and in the case of Ti-5Mo-4Fe #3 to #6, the precipitation and growth of TiFe were observed.
[0049] Furthermore, an increase in the size of certain pores was observed under some post-heat treatment conditions; this appears to be due to the active diffusion during post-heat treatment, which brings adjacent pores closer together and causes them to merge. The surface of a pore, being the interface between solid and gas, has broken atomic bonds and possesses higher surface energy than a normal crystal structure; therefore, the structure changes in a direction that minimizes this surface energy during post-heat treatment. Consequently, small pores with high curvature merge into larger pores, and while the merged pores transform into a single, relatively larger pore, the overall porosity decreases and the structure is simplified. This phenomenon lowers the total surface energy of the pores and contributes to the improvement of the thermodynamic stability of the pore structure. Additionally, a phenomenon in which pores are partially filled due to diffusion induction during post-heat treatment... It was observed in Figures 3 and 4.
[0050] mechanical properties
[0051] Vickers hardness measurements and room temperature compression tests were performed on Ti-5Mo-xFe (x=2.4wt%) alloys, and the Vickers hardness measurement results are The results are shown in 5, 6 and Table 3. As a result of Vickers hardness measurements, the Ti-5Mo-4Fe alloy exhibited a hardness value approximately 78.5 Hv higher than that of the Ti-5Mo-2Fe alloy. It is believed that the thin α-lamellar lath spacing and solid solution strengthening effect of the Ti-5Mo-4Fe alloy contributed to the improvement in hardness. The lamellar structure consists of different crystal directions or α / β boundaries, which act as obstacles that make it difficult for dislocations to pass through due to differences in interfacial energy and elastic constants. As the spacing narrows, the boundary area per unit volume increases, resulting in an increase in hardness.
[0052] Sample name Hardness value Standard deviation (Hv) Ti-5Mo-2Fe Ti-52 235.36 ±27.85 Ti-52 #1 311.12 ±35.85 Ti-52 #2 318.04 ±49.66 Ti-52 #3 331.77 ±32.96 Ti-52 #4 349.16 ±55.28 Ti-52 #5 331.14 ±44.80 Ti-52 #6 357.09 ±36.98 Ti-5Mo-4Fe Ti-54 313.82 ±27.85 Ti-54 #1 364.65 ±39.12 Ti-54 #2 343.76 ±31.44 Ti-54 #3 420.04 ±37.88 Ti-54 #4 402.64 ±34.76 Ti-54 #5 412.77 ±37.15 Ti-54 #6 430.96 ±33.38
[0053] When comparing the alloys that underwent post-heat treatment, Ti-5Mo-4Fe #6 exhibited the highest hardness value of 430.96 Hv, which showed the greatest reduction in porosity. This appears to be due to the fact that the pore size measured under the Ti-5Mo-4Fe #6 condition was the smallest at approximately 7.2 μm, contributing to the increase in hardness. Furthermore, under the overall post-heat treatment conditions of the Ti-5Mo-4Fe alloy, the increased Fe content compared to the Ti-5Mo-2Fe alloy resulted in relatively superior hardness values.
[0054] Corrosion characteristics
[0055] To evaluate the corrosion characteristics of the Ti-5Mo-xFe (x=2,4wt%) alloy, potentiodynamic polarization experiments and potentiodynamic polarization experiments were conducted on materials under conditions #1 and #6, which had the largest and smallest reductions in porosity after the original material and post-heat treatment, and the results are shown in Figures 7 to 10 and Table 4.
[0056] E corr (V) I corr (A / cm 2 ) Corrosion rate (mmy -1 ) Ti-52 -0.664 1.11×10 -6 1.423×10 -10 Ti-52 #1 -0.166 5.62×10 -7 6.94×10 -11 Ti-52 #6 -0.195 4.54×10 -9 5.64×10 -13 Ti-54 -0.669 2.41×10 -7 2.91×10 -10 Ti-54 #1 -0.108 7.42×10 -8 8.72×10 -11 Ti-54 #6 -0.153 3.18×10 -9 3.77×10 -13
[0057] The corrosion characteristics of the Ti-5Mo-xFe (x=2.4wt%) alloys exhibited excellent corrosion properties as the porosity decreased. Since the interior of the pores is an environment with limited oxygen supply, electrochemical conditions different from the exterior are formed; consequently, the interior of the pores becomes the cathode and the exterior the anode, leading to localized corrosion.
[0058] Titanium alloys generally exhibit excellent corrosion resistance due to the formation of a TiO2 passivation film; however, the film near pores is not uniformly formed and can fracture. Consequently, localized corrosion and mechanical damage may occur in the fractured sections of the passivation film. Furthermore, typical pores form stress concentration points within the material and trigger stress corrosion cracking when exposed to corrosive environments.
[0059] As a result of potentiodynamic polarization experiments, the oxidation behavior of the Ti-5Mo-2Fe base material and Ti-5Mo-4Fe #6 conditions showed a tendency for current density to increase sharply in the range above a certain potential, which appears to indicate the occurrence of localized corrosion. However, no slowdown or plateau phenomenon was observed above that potential; it is judged that these phenomena were caused by the aforementioned pores inducing non-uniformity and localized damage to the passivation film, thereby sustaining unstable oxidation behavior.
[0060] Subsequently, the experimental results of the two conditions with the highest reduction in porosity in each alloy system, Ti-5Mo-2Fe #6 and Ti-5Mo-4Fe #6, were compared and evaluated, and are shown in Figure 11. Although the porosity of the Ti-5Mo-4Fe #6 condition was the lowest at approximately 7%, it showed results almost similar to those of the Ti-5Mo-2Fe #6 condition. This suggests that as the Fe content increases, intermetallic compounds such as TiFe become more prone to precipitation; these precipitates reduce the ability to form a passivation film and cause galvanic corrosion, which is believed to have acted as a cause of reduced corrosion resistance.
[0061] The results of the analysis described above are summarized as follows.
[0062] The post-heat treatment process was effective in reducing porosity overall, and showed the largest reduction (-8%) under the Ti-5Mo-4Fe #6 condition treated at a temperature above the β transformation point and for a long time.
[0063] Under post-heat treatment conditions below the β transformation point, an α+β lamellar structure was observed, and the lamellar spacing decreased as temperature and time increased. In addition, above the β transformation point, an equiaxed β phase structure was observed, along with TiFe precipitates.
[0064] Both hardness and compressive strength improved under conditions of increased Fe content and high-temperature post-heat treatment, with the highest hardness (430.96 Hv) and compressive strength (1144.93 MPa) observed under the Ti-5Mo-4Fe #6 condition. This is attributed to the narrow lamellar lath spacing, low porosity, and the strengthening effect of precipitates.
[0065] Under conditions where porosity was reduced through post-heat treatment, overall corrosion resistance improved; however, the Ti-5Mo-4Fe #6 condition, which has a high Fe content, exhibited corrosion behavior similar to the Ti-5Mo-2Fe #6 condition due to non-uniformity of the passivation film caused by TiFe precipitation and micro-galvanic effects. This indicates that an increase in Fe content can have a negative impact on corrosion resistance.
Claims
Claim 1 (a) a step of preparing titanium powder through an HDH (hydrogenation-dehydrogenation) process; (b) a step of preparing a mixed powder by mixing the titanium powder with Mo powder and Fe powder; (c) a step of manufacturing a titanium alloy by compressing and sintering the mixed powder; and (d) post-heat treating the manufactured titanium alloy at a temperature above the β-transformation temperature so that the corrosion current density (Icorr) becomes 1.0 × 10⁻⁶ -8 A method for manufacturing a titanium alloy, comprising the step of reducing the porosity to A / cm² or less and the Vickers hardness to 400 Hv or more. Claim 2 A method for manufacturing a titanium alloy according to claim 1, wherein the titanium alloy comprises 2.0 wt% to 7.0 wt% molybdenum (Mo), 1.5 wt% to 5.0 wt% iron (Fe), and the remainder being titanium (Ti) and unavoidable impurities. Claim 3 A method for manufacturing a titanium alloy according to claim 1, wherein the titanium alloy comprises 4.0 to 6.0 weight% molybdenum (Mo), 3.5 to 4.5 weight% iron (Fe), and the remainder being titanium (Ti) and unavoidable impurities. Claim 4 A method for manufacturing a titanium alloy according to claim 1, wherein the post-heat treatment is performed in a temperature range of 800°C to 950°C. Claim 5 A method for manufacturing a titanium alloy according to claim 1, wherein the post-heat treatment is performed for 30 minutes to 4 hours. Claim 6 A method for manufacturing a titanium alloy according to claim 1, wherein step (c) comprises: a step of compression molding the mixed powder; and a step of sintering the compression-molded alloy at 1200°C to 1300°C. Claim 7 A method for manufacturing a titanium alloy according to claim 1, characterized in that the porosity of the titanium alloy is reduced to 20% or less after the post-heat treatment. Claim 8 Manufactured by the method according to Claim 1, having a composition consisting of 4.0 wt% to 6.0 wt% molybdenum (Mo), 3.5 wt% to 4.5 wt% iron (Fe), and the remainder being titanium (Ti) and unavoidable impurities, having a microstructure comprising equiaxed β phase and TiFe precipitates, a porosity of 13% or less, a Vickers hardness of 400 Hv or more, and a corrosion current density (Icorr) of 1.0 × 10⁻⁶ -8 Titanium alloy with an A / cm² or less. Claim 9 In claim 8, the corrosion current density (Icorr) of the titanium alloy is 1.2×10 -8 Titanium alloy with an A / cm² or less.
